Controle varietal e bioatividade do óleo essencial de Lippia gracilis no manejo de Raoiella indica (Acari: tenuipalpidae) - Santos, Maria Clezia dos (2018)
Red palm mite, Raoiella indica (Acari: Tenuipalpidae), is a polyphagous pest that feeds via the stomata of host plants, such as coconut (Cocos nucifera L.). Among the available methods for integrated pest management, plant resistance and botanical pesticides can be adopted to reduce problems associated with R. indica infestation. This study aimed to evaluate the natural infestation of R. indica in accessions of dwarf coconut of the green, red, and yellow subvarieties, as well as the efficiency of the essential oil of Lippia gracilis (Verbenaceae) and its major compound (thymol) against this pest and their compatibility with the predatory mite Amblyseius largoensis (Acari: Phytoseiidae). Population densities of red palm mite (eggs and active stages) were evaluated in the following dwarf coconut accessions: Brazilian Green Dwarf Jequi (BGDJ); Cameroon Red Dwarf (CRD); Malayan Red Dwarf (MRD); Brazilian Red Dwarf Gramame (BRDG); Brazilian Yellow Dwarf Gramame (BYDG); and Malayan Yellow Dwarf (MYD). The evaluations were performed at the International Coconut Germplasm Bank for Latin America and the Caribbean (ICG-LAC), located in the experimental field of Embrapa, in Itaporanga D'Ajuda, SE. R. indica infestation was influenced by the dwarf coconut subvariety. Therefore, the BGDJ (green) accession had lower population densities when compared with the BYDG (yellow) and BRDG (red) accessions. Additionally, the number of eggs and active stages of R. indica found in the dwarf coconut accessions was not correlated with the density of stomata, which contrasts with the hypothesis that the population density increases with the increase in the number of stomata. The LC50 (4.995 mg/mL) detected for the essential oil of the L. gracilis genotype LGRA-106, against R. indica was lower than the LC50 (9.028 mg/mL) of thymol; however, no difference was observed for their toxicity. This oil showed acute mortality to R. indica within the first hour after spraying, and its residual effect was lost after nine hours. In addition, the oil reduced the survival and reproduction of R. indica, but it was toxic to the predatory mite. Results concluded that the BGDJ accession, belonging to the green subvariety, and the essential oil of L. gracilis are promising for the management of R. indica.